The Effect of V-Bending Parameters Utilizing Electrolytic Zinc-Coated Steel Sheet (SECC) Material: Pengaruh Variasi V-Dies Bending Angle pada Material Electrolytic zinc-coated Steel Sheet (SECC) - Dodi Mulyadi; Khoirudin; Sukarman; Mohamad Rizkiyanto; Nana Rahdiana; Ade Suhara; Ahmad Fauzi; Sumanto (Fakultas Teknik Universitas Pancasila, 2023)
This study discusses the phenomenon of spring-back and spring-go in the bending kinematic forming using V-bending dies process and Electrolytic zinc-coated steel sheet (SECC/JIS G 3313) material. The zinc layer on the galvanized steel surface should not be damaged during the material forming process. The zinc layer on the galvanized steel sheet will affect the metal forming process. This study uses an experimental design with four input parameters, namely v-die opening L (mm), punch angle (degree), punch speed (mm/minutes), and bending force (kN). The smallest spring-back was obtained in the 4th test sample: the v-die opening of 35 mm, the punch angle of 40o, the punch speed of 30 mm/minute, and the bending force of 7.50 kN. The minor spring-back degree was 1.67o. Meanwhile, the smallest spring-go obtained in the second sample, namely the v-die opening of 30 mm, the punch angle of 50o, the punch speed of 40 mm/minute, and the bending force of 7.00 kN, the minor spring-go degree of 0.92o was obtained. These results show that the best spring-back degree for SECC/JIS G 3313 material is obtained when the bending process is performed with the v-die bending parameter of 30 mm, punch angle of 50o, punch speed of 40 mm/minute, and bending force of 7.00 kN.